1997
DOI: 10.1139/b97-065
|View full text |Cite
|
Sign up to set email alerts
|

Inflorescence and flower development in the Hedychieae (Zingiberaceae): Hedychium

Abstract: Flower organogenesis in Hedychium gardnerianum and Hedychium coronarium begins with the sequential formation of the sepals on a rounded–triangular apex. Growth in three regions of the apex, inside the sepals, produces three common petal – inner androecial primordia. Intercalary growth below and between these primordia produces a floral cup, the site of gynoecial formation. The common primordia separate to form petals and inner androecial members. After separation, the anterior inner androecial members fuse to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 27 publications
2
41
0
2
Order By: Relevance
“…Liao et al (2006) supposed the labellum represents the five members of the androecium based on the studies of floral vasculature. The floral development studies reported by Kirchoff (1997Kirchoff ( , 1998 and Song et al (2007) supported the interpretation that the labellum is derived from the congenial fusion of two inner staminodes, and the abaxial outer androecial member contributes only initially to the formation of the labellum.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Liao et al (2006) supposed the labellum represents the five members of the androecium based on the studies of floral vasculature. The floral development studies reported by Kirchoff (1997Kirchoff ( , 1998 and Song et al (2007) supported the interpretation that the labellum is derived from the congenial fusion of two inner staminodes, and the abaxial outer androecial member contributes only initially to the formation of the labellum.…”
Section: Discussionmentioning
confidence: 68%
“…1). In spite of quite a few different opinions presented in the past about the nature of labellum based on the morphological and anatomical evidence (Rao 1963;Burtt 1972), the recent evidence on floral organ development supported the notion that the labellum was derived from the congenial fusion of the inner staminodes (Kirchoff 1997(Kirchoff , 1998Song et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The plant habit ranges from terrestrial to epiphytic as well as lithophytic and each plant has a perennial rhizome which bears new ramets annually. Each ramet gives rise to a terminal inflorescence (known as thyrse) which consists of primary inflorescence bracts that hold flowers in cincinni (Kirchoff 1997). Two main types of inflorescence bracts are identified in Hedychium - imbricate (where bracts are broad and overlapping, hiding the rachis) and folded (where bracts are narrow and fold partially or completely to enclose the flowers, leaving rachis visible, Holttum 1950).…”
Section: Introductionmentioning
confidence: 99%
“…However, a correlation between flower position in inflorescence and orientation of its symmetry plane is documented in some angiosperms. In several members of Zingiberales that bear thyrses with lateral cincinni, flowers of successive orders in a cincinnus change their symmetry plane orientation between median and transversal, so that symmetry planes of all flowers are parallel to each other (KUNZE 1985;KIRCHOFF 1997KIRCHOFF , 1998KIRCHOFF , 2000. Interestingly, due to this kind of flower arrangement and symmetry, the only stamen of each flower is in the position closest to the main axis of the inflorescence (e.g., Hedychium: KIRCHOFF 1997, 2000.…”
Section: Discussionmentioning
confidence: 99%